Fighting for partnership : labor and politics in unified Germany - Turner, Lowell (Cornell studies in political economy., 1998)
Lowell Turner has extensively researched the German transformation in the 1990s. Indeed, in 1993 he was at the factory gates at Siemens in Rostock for the first major strike in post-Cold War eastern Germany. In that strike, and in a series of other incisively analyzed workplace and job developments in eastern Germany, he shows the remarkable resilience and flexibility of the German social partnership and the contribution of its institutions to unification. His controversial and, to some, radical findings will stimulate debate at home and abroad.